2013
DOI: 10.2298/avb1301101z
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion body hepatitis (IBH) outbreak associated with fowl adenovirus type 8b in broilers

Abstract: The causative agent of inclusion body hepatitis (IBH) was identified as fowl adenovirus (FAdV) type 8b, a member of the Fowl adenovirus E species, based on PCR results of adenoviral polymerase and the hexon gene in an outbreak of acute mortality that affected a broiler flock of 12,000 animals. In two waves of elevated mortality rate, a total of 264 chickens were found dead. Affected birds showed ruffled feathers, depression, watery droppings and limping. The most common pathological lesions seen on necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…An enlarged spleen is rarely reported in association with IBH in the literature Zadravec et al, 2013), and when reported has been more frequently associated with HPS (Cowen, 1992;Asrani et al, 1997). The observation of an enlarged spleen at necropsy in FAdV-8b and FAdV-11 inoculated birds in this study coincided with the histological observation of morphological changes of some cells and depletion of the white pulp, as well as the observation of INIBs in the liver.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…An enlarged spleen is rarely reported in association with IBH in the literature Zadravec et al, 2013), and when reported has been more frequently associated with HPS (Cowen, 1992;Asrani et al, 1997). The observation of an enlarged spleen at necropsy in FAdV-8b and FAdV-11 inoculated birds in this study coincided with the histological observation of morphological changes of some cells and depletion of the white pulp, as well as the observation of INIBs in the liver.…”
Section: Discussionsupporting
confidence: 85%
“…FAdV-8b and FAdV-11 have been identified in several countries in association with IBH (Ojkic et al, 2008;Lim et al, 2011;Zadravec et al, 2011;Hess, 2013), as well as with HPS (Nakamura et al, 2000) and gizzard erosion (Okuda et al, 2004). The primary purpose of this investigation was to determine if field strains of FAdV-1, FAdV8b and FAdV-11, all isolated in association with IBH field outbreaks without evidence of immunosuppression, are primary pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, IBH outbreaks caused by different FAdV serotypes have been described in Canada (Philippe et al, 2005;Ojkic et al, 2008a, b;Grgic et al, 2011;Dar et al, 2012), the USA (Wilson et al, 2010), the Republic of Korea (Choi et al, 2012), India (Thakor et al, 2012), South Africa (Joubert et al, 2014), Japan (Nakamura et al, 2011), China (Zhao et al, 2015), Australia (Steer et al, 2011) and in some European countries (Pizzuto et al, 2010;Zadravec et al, 2011Zadravec et al, , 2013Kajan et al, 2013;Schachner et al, 2016). Most of these outbreaks have been associated with genotypes FAdV-D, -E or -C, with serotypes 2, 4, 8b and 11 being the most frequently involved.…”
Section: Discussionmentioning
confidence: 99%
“…E.g. recent research shows that only specific and not all serotypes of the species Fowl aviadenovirus D and E cause inclusion body hepatitis in chicken (Schachner et al 2018;Zadravec et al 2011). But recent host switches might result in an elevated pathogenicity (Benkő and Harrach 2003;Jánoska et al 2011;Kohl et al 2012;Vidovszky et al 2015).…”
Section: Adenovirusesmentioning
confidence: 99%